Indeks Kepuasan Masyarakat Untuk Mengukur Pelayanan Publik Pada Kantor Kecamatan Kabupaten Soppeng - Hasanuddin (Insan Cita Bongaya Research Journal, 2022)
The purpose of this study was to measure the management of public services provided to the community at the sub-district office in Soppeng district. The research data were obtained in 8 sub-districts in the Soppeng Regency. Data is collected using . The technique of collecting research data is to use a survey by distributing closed and structured questionnaires as a tool to reveal answers from respondents. The data analysis technique is using the IKM value which is calculated using the weighted average value of each service element. The results showed that there are 2 sub-districts that get a Conversion Interval value of 65.00 – 76.60, namely LILIRIAJA District and LILIRILAU District with Service Quality